Analysis of the Influence of Agricultural Product Yields, Income and Zakat Awareness on Compliance in Paying Agricultural Zakat (Case Study of Farmers in Lingga Julu Village, Karo Regency) - Asryatun Nisa Br Ginting; Waizul Qarni; Rahmi Syahriza (Indonesian Journal of Islamic Economics and Finance, 2026)
This study was conducted to analyze and measure the influence of agricultural production, income level, and zakat awareness on the community’s compliance with the obligation to pay agricultural zakat in Lingga Julu Village, Karo Regency. Data analysis in this study utilized multiple linear regression with the assistance of IBM SPSS Statistics software. Based on the test results, an Adjusted R-Square value of 0.419 or 41,9% was obtained. This value indicates that the variables of agricultural production, income, and zakat awareness account for 41,9% of the variation in compliance with paying agricultural zakat, while the remaining 58,1% is influenced by other factors outside the scope of this study. At a 95% confidence level with a 5% significance level, the results of the partial tests show that agricultural production, income, and zakat awareness each have a positive and significant effect on zakat payment compliance. Furthermore, the results of the simultaneous test showed an F-calculated value of 15.166 > F-table 2.769 with a significance value of 0.000 < 0.05, indicating that these three variables collectively have a significant effect on the community’s compliance with paying agricultural zakat.